1992
DOI: 10.1161/01.hyp.19.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine and the genesis of hypertension.

Abstract: Several lines of evidence suggest a psychophysiological link between stress, adrenomedullary activation, and the genesis of hypertension. Experimental data support four important concepts: 1) epinephrine stimulates prejunctional beta 2-adrenergic receptors that facilitate norepinephrine release from sympathetic nerve endings; 2) epinephrine can be converted into a cotransmitter by neuronal uptake and on subsequent release augment the simultaneous discharge of norepinephrine; 3) exogenous epinephrine can induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
4

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(52 citation statements)
references
References 140 publications
1
47
0
4
Order By: Relevance
“…24 Plasma noradrenaline levels provide a clinically useful index of sympathetic nervous system activity in human subjects. 25,26 Villecco et al 27 used a headup tilt test as a physiological stimulus to study blood pressure, heart rate, and plasma noradrenaline in women. They demonstrated that hypertensive women (both pre-and postmenopausal) had a significantly greater increase in noradrenaline secretion after physiological stimulation than normotensive women (P Ͻ 0.01) (Figure 3).…”
Section: Pathophysiologymentioning
confidence: 99%
“…24 Plasma noradrenaline levels provide a clinically useful index of sympathetic nervous system activity in human subjects. 25,26 Villecco et al 27 used a headup tilt test as a physiological stimulus to study blood pressure, heart rate, and plasma noradrenaline in women. They demonstrated that hypertensive women (both pre-and postmenopausal) had a significantly greater increase in noradrenaline secretion after physiological stimulation than normotensive women (P Ͻ 0.01) (Figure 3).…”
Section: Pathophysiologymentioning
confidence: 99%
“…25 We demonstrated that the arteries from LPAR1-deficient mice became less responsive to phenylephrine stimulation in contraction, Figure 2. Null function of LPAR1 reduced blood pressure and inhibits sleep deprivation-induced blood pressure elevation and phenylephrine-induced vasoconstriction.…”
Section: Discussionmentioning
confidence: 86%
“…25 We demonstrated that the arteries from LPAR1-deficient mice became less responsive to phenylephrine stimulation in contraction, Two hundred seventy-eight healthy individuals were randomly recruited, and rs531001 was genotyped by direct sequencing. The individuals were divided into GG, CG, and CC groups.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] According to the "epinephrine hypothesis" of hypertension, epinephrine, released from the adrenal medulla during physiological stress, is taken up into sympathetic nerve terminals and later rereleased with norepinephrine (NE) as a cotransmitter. The epinephrine that has been rereleased stimulates further NE release through its action on presynaptic ␤-adrenergic receptors and in this way amplifies and prolongs sympathetic responses.…”
mentioning
confidence: 99%
“…The epinephrine that has been rereleased stimulates further NE release through its action on presynaptic ␤-adrenergic receptors and in this way amplifies and prolongs sympathetic responses. 1,4,5 Therefore, a brief increase in epinephrine concentrations, such as occurs in response to stress, could, through the mechanisms of uptake, rerelease, and stimulation of NE release, amplify and prolong sympathetic responses and facilitate the development of hypertension. 1,3,4 Experimental evidence supports the existence of functional presynaptic ␤-adrenergic receptors as well as the process of uptake and rerelease of epinephrine in the nerve terminal [5][6][7][8][9][10] : mechanisms that would allow epinephrine to produce a delayed and sustained facilitatory effect on NE release.…”
mentioning
confidence: 99%